Sharia Philosophy Correlation and the Islamic Economic Philosophy - Hendrianto Hendrianto; Juhaya S. Praja; Nurrahman (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
This study aims to reveal the relationship between Islamic philosophy and Islamic economic philosophy, both in terms of foundation, operation, and objectives. This library research (Library Research) uses documentation data collection techniques with data analysis, namely content analysis. The results showed that the relationship between sharia philosophy and sharia economic philosophy is that there is a philosophical foundation based on al-qur'am, hadith, ijma 'and qiyas, as well as operational principles, observations are made, take generalization conclusions and serve as theory, while the goal is both want to get happiness in the world and the hereafter, but what distinguishes the two lies in the broader study of sharia philosophy and complexity, while Islamic economic philosophy specializes in sharia economic studies. But for sharia economic philosophy discusses tauhid, caliphate, tazkiyah, and masuliyya. Operational principles, observing, drawing conclusions and making theory. The goal of obtaining falah, namely survival, freedom of desire, and strength and honor.